(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article discusses current aspects of the digital transformation of the economy of the Donetsk People’s Republic. As part of the research topic, the share of the digital economy of the world’s leading economies in terms of GDP was determined. The goals of digital transformation are revealed at such levels as: public administration, industry, regional administration, regional executive authorities, organizations. The main barriers preventing the digital transformation of the DPR economy have been identified. In accordance with the ROCIT methodology, the level of basic digital literacy of the population of the DPR was analyzed. A strategic model of digital transformation of sectors of the economy, social sphere and public administration of the Donetsk People’s Republic is presented.